ACCOUNTABILITY AND TRANSPARENCY OF POLITICAL PARTY ASSISTANCE FUNDS IN NORTH LAMPUNG - Pribadi Atur Wibowo; Agus Purnomo (International Journal of Multidisciplinary Reseach, 2026)
This study analyzes accountability and transparency in the management of political party assistance funds at the National Unity and Politics Agency of North Lampung Regency. The research uses a descriptive qualitative approach to examine how financial accountability, administrative accountability, information transparency, procedural transparency, and accountability mechanisms are implemented in the distribution, use, reporting, and supervision of public funds for political parties. Data were collected through interviews with relevant officials and document studies related to party assistance funding. The findings show that the management of political party assistance funds has generally followed the applicable regulatory framework, particularly in administrative verification, fund distribution, guidance, and accountability reporting. However, several aspects still require strengthening, including human resource capacity, documentation quality, public access to information, and consistent reporting discipline by political parties. The study concludes that accountable and transparent management is essential to strengthen good governance, prevent misuse of public funds, and increase public trust in political party financing.